Regression analysis of cyber attacks development trends - Аксьончиков, Святослав; Ємельянова, І. В.; Маркова, Катерина; Сватовський, Ігор (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2017)
The article gives a justification for conducting a regression analysis of trends in the development of cyber attacks. Factors which are likely to affect most the fluctuations in the intensity of attacks have been selected. Correlation and regression analysis of factors which influence the number of cyber attacks on web-resources have been carried out by using the statistics for a few previous years. The adequacy of the obtained models has been checked and the possibility of using the obtained data to improve the protection of web-resources has been proved. Conclusions regarding the obtained results are made and the ways of increasing the reliability of the results in further research are substantiated.